Characterization of feline Borna disease virus - Oladele, Oluwafemi (2011)
Feline Borna disease, a neurological disease of cats is an infection caused by Borna disease virus (BDV). The infection, first reported in Sweden in 1974, affects other species of animals such as horses in which the disease was first reported. Sheep is the other natural host of the virus, but BDV infection is also seen in cattle, dogs, goats, donkey, and some zoo animals. The disease is widely speculated to be zoonotic as it is believed to affect humans as well. In Sweden, the infection is endemic in central part of Sweden namely in the Stockholm and Uppsala area, where numerous cases have been reported in the past and new cases continue to emerge in recent times. The importance and continued incidence and prevalence of the infection in cat prompted this present study. Archive and incoming samples from cats, horses and dogs were screened by real- time RTPCR. Eight positive cat samples were detected by real-time RT-PCR. Three of these samples were used for virus isolation and characterization, while two other positive samples were used to test previously described primers. In conclusion, we have been able to detect eight positive samples from the cat by real-time RT-PCR. Though the virus was not detected upon sub-passages in vero cells, demonstration of presence of the virus from passage 10-12 in the positive control show that other factors than the assay may have contributed to the lack of virus isolation The classical PCR for molecular epidemiology needs further optimization as reflected in the fact that only three primer pairs seem to work with the C6BDV control